Education Of Students Majoring In "Physical Education And Sports" On The Knowledge Of Olympic Education (On The Example Of Yuriy Fedkovych Chernivtsi National University) - BALATSKA, LARISA; Moseychuk, Yurii; Moldovan, Andrii; NAKONECHNYI, IHOR; Горюк Goriuk, Петро Petro; DOTSYUK, LIDIIA; Vaskan, Ivan (7th International Conference of the Universitaria Consortium In Physical Education, Sports and Physiotherapy, Iasi, Romania, 2021)
To cherish the ideals, symbols of Olympism, one of the tasks of education in the upbringing and training of the younger and juvenile generation. In different countries of Europe and the world, education on the knowledge of Olympism is carried out through Olympic education programs for different groups of the population (preschoolers, schoolchildren, students, etc.). At various levels of government, from the United Territorial Communities (UTCs) to the Ministry of Education and Science (MES) in Ukraine more and more time is devoted to studying, consolidating knowledge about the values and ideals of Olympism, which is manifested in the organization of different events by the National Olympic Committee: "Olympic treatment", "Olympic lesson", "OlimpicLab", etc. Theoretical knowledge of the younger generation on ideals and symbols, as practice shows, requires deeper, even greater training, as well as knowledge. Highly qualified specialists in the field of physical culture and sports who successfully master the material, the program of preparation of both practical and theoretical knowledge will help to increase the percentage on this issue.
Keywords: knowledge; ideals; Olympic education; students